Leadership and Management Dynamics and Their Multifaceted Impact on Quality Education in Selected Mogadishu Private Universities - Sheye, Hussein Abdule (2024)
This study examined the impact of leadership and management dynamics on providing quality education at private universities in Mogadishu. The IV of the study was the deans' and vice-chancellors' managerial skills, leadership styles, the dynamics of internal management practices including climate, culture, change, and conflict, and the dynamics of managerial activities containing physical, human, financial, curriculum, administrative, and university-community relations. The study also examined institutional constraints (MV) that affected the relationship between the IV and the DV. The study was theoretically grounded in Prinsloo's model, which was developed in the setting of South Africa. The research instruments employed were a cross-sectional survey design consisting of questionnaires and interviews. The priority was given to the quantitative methodology. Since the research hypotheses were concerned with assessing relationships, Pearson’s Correlation was used. The results indicated a positive correlation. The dynamics of managerial activities yielded the following results: M=3.5, SD=0.81 and p<0.000, r=0.617. The areas that needed improvements in the qualitative data included curriculum implementations, and conducting impactful applied research. The findings for the internal management practices were: M=3.39, SD=0.72 and p<0.000, r=0.575. The qualitative data showed that policies for punctuality and staff promotion needed to be rectified. The results for the managerial skills were: M=3.69, SD=0.87 and p<0.000, r=0.472. The qualitative data revealed that coordination and delegation needed to be upgraded. The findings for the leadership styles were M = 2.9, SD = 1.18, and p <0.000, r = .0593. The predictor variables alone accounted for 46.7% of the variation in the quality of education. When institutional constraints e.g. insecurity, funding source, regulatory bodies, and the quality of education of secondary school graduates were included in the regression model, the adjusted R² value increased to 57.4%. In the context of Somalia, the institutional constraints should be incorporated into Prinsloo's model. In summary, the study extended and strengthened the theoretical foundation of Prinsloo's Model. The findings could serve as a foundational resource for future academic research. The findings may be valuable to scholars, students, policymakers, university administrators, and the Ministry of Education.